TINJAUAN PENDEKATAN ETNOMEDIS: PRODUK TANAMAN SEDATIF ALAMI UNTUK PENGOBATAN GANGGUAN KECEMASAN - Dita Sheilla Putri Wahyuningtias; Putu Desy Sagita Ananda; Laurens Frestasya A. Turnip (STKIP Subang, 2026)
Anxiety disorders are common psychiatric conditions associated with significant disability, influenced by a complex interplay of genetic, environmental, and epigenetic factors. Current first-line treatments, including Selective Serotonin Reuptake Inhibitors (SSRIs), Serotonin Norepinephrine Reuptake Inhibitors (SNRIs), and benzodiazepines, remain limited in efficacy and are associated with adverse effects such as addiction, particularly with benzodiazepine use, highlighting the need for novel pharmacological agents derived from natural compounds. Therefore, this review aimed to provide a comprehensive overview of natural compound-based drugs investigated in clinical trials for their potential in treating fear, anxiety, and trauma-related disorders, conducted through a systematic literature search of PubMed, Google Scholar, and Scopus databases using the keywords